2021
DOI: 10.35551/pfq_2021_s_2_5
|View full text |Cite
|
Sign up to set email alerts
|

Government Internal Control System and Local Government Administration Performance: Evidence from Indonesian Local Governments

Abstract: This study investigates the effect of local government internal control systems on local government administration performance. We use secondary data from the Ministry of Internal Affairs, Financial and Development Supervisory Agency, Indonesian Statistics Bureau, and respective local government financial statements and websites. We generate a set of panel data from 508 local governments during 2017-2019 with 1524 observations analysed with panel data regression. We evidence that several local governments stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
1
12
0
1
Order By: Relevance
“…From accounting perspective, local governments have the authority to manage the allocation of the budget for the sake of human development (Prabowo, Leung & Guthrie, 2017). Further, the governance factor specifically the role of government supervision agencies is also very crucial (Winarna et al, 2021). This factor matters in determining local government accountability (Nurdiono & Gamayuni, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…From accounting perspective, local governments have the authority to manage the allocation of the budget for the sake of human development (Prabowo, Leung & Guthrie, 2017). Further, the governance factor specifically the role of government supervision agencies is also very crucial (Winarna et al, 2021). This factor matters in determining local government accountability (Nurdiono & Gamayuni, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of a local government public service can be measured by how well the organizers of government agencies carry out their duties and authority to the community and the level of community satisfaction with services provided by local and central governments. Service quality is also essential in implementing a public service in Indonesia (Hadian, 2017;Martani et al, 2014) A poor public service reputation is permanently attached to the reputation of the Indonesian government's public service providers; it can be concluded that local government public services are vital for the community, so measurement is needed to measure the quality of public services (McLaren et al, 2019;Winarna et al, 2021a). The practice of maladministration in government public services does not only lead to corruption and bribery, but this practice can hinder government investment and development, especially in the area of local government.…”
Section: Introductionmentioning
confidence: 99%
“…to be much more leverage(Dba et al, 2021;Steven DeSimone & Sarens, 2019)If the maturity level is high, it can be said that the government can conduct a more comprehensive and more accurate study(Hamid, 2013;Winarna et al, 2021a). In conclusion, if the SPIP maturity level is an internal audit of the Makassar local government, it can be a success for the local government to implement accrual-based Government Accounting Standards (ASP) so that the output is expected to have a positive impact on public services (Dba et al, 2021;Winarna et al, 2021a)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These systems start from introducing concepts and guidelines to measuring the implementation success with methodologies that measure the government's internal control system's role in supporting public finance administration's accountability. Winarna, Muhtar, Sutaryo, and Amidjaya (2021) examined the influence of the local government's internal control system on the performance of government administration. They proved that the control environment, risk assessment, information, and communication positively affect the performance of local government administration.…”
Section: Introductionmentioning
confidence: 99%